Multiple drug use disorder diagnoses among drug-involved hospitalizations in the United States: Results from the 2016 National Inpatient Sample. (1st August 2020) - Zhu, He; Wu, Li-Tzy
Highlights: 1 in 2 drug-involved hospitalizations had multiple drug use disorder (DUD) diagnoses. Opioid use disorder was the leading DUD among drug-involved hospitalizations. 51 % of opioid-involved hospitalizations had multiple DUD diagnoses. Young adults aged 18−25 (vs. ≥ 26) were more likely to have multiple DUD diagnoses. Having mental disorders were more likely to have multiple DUD diagnoses. Abstract: Background: Having more than one drug use disorders (DUDs) is an increasing public health concern, but it has been understudied. The goal of this study is to investigate the prevalence and patterns of coexisting DUD diagnoses among inpatient hospitalizations due to DUD in the United States. Methods: Data were from the 2016 National Inpatient Sample and included hospitalizations with a principal DUD diagnosis for patients aged ≥18 years (i.e., drug-involved hospitalizations, unweighted n = 31, 707). The DUD diagnosis profile was categorized into three groups: single, two, and three or more DUD diagnoses. Generalized ordered logit models were used to examine correlates of DUD diagnosis groups. Results: Among drug-involved hospitalizations, approximately 50.1 % had multiple coexisting DUD diagnoses (2 DUD diagnoses, 32.1 %; ≥3 DUD diagnoses, 18.0 %). Particularly, opioid use disorder accounted for 58.6 % of drug-involved hospitalizations. Among specific opioid-involved hospitalizations, about 51.2 % had multiple DUD diagnoses. The most common secondary DUD diagnoses among opioid-involved hospitalizations included cocaine (21.7 %), cannabis (18.5 %), and sedatives (18.1 %). Adjusted analyses showed that being aged 18−25 years (vs. ≥ 26), living in areas with the lowest quartile of household income (vs. highest), and having a secondary diagnosis of mental disorders or tobacco/alcohol use disorder were associated with increased odds of having multiple DUD diagnoses in the total sample and in the opioid subsample. Conclusions: Findings suggest that healthcare providers should increase the awareness of multiple DUDs while treating patients with DUD, especially those with opioid use disorder. More research is needed to better characterize treatment needs for patients with multiple DUDs.